Pre-exposure prophylaxis uptake among Black/African American men who have sex with other men in Midwestern, United States: a systematic review - Oluwafemi Adeagbo; Oluwaseun Abdulganiyu Badru; Prince Addo; Amber Hawkins; Monique Janiel Brown; Xiaoming Li; Rima Afifi (Frontiers in Public Health)
IntroductionBlack/African American men who have sex with other men (BMSM) are disproportionately affected by HIV, experience significant disparities in HIV incidence, and face significant barriers to accessing HIV treatment and care services, including pre-exposure prophylaxis (PrEP). Despite evidence of individual and structural barriers to PrEP use in the Midwest, no review has synthesized this finding to have a holistic view of PrEP uptake and barriers. This review examines patterns of, barriers to, and facilitators of PrEP uptake among BMSM in the Midwest, United States (US).MethodsFive databases (CINAHL Plus, PUBMED, PsycINFO, SCOPUS, and Web of Science) were searched in March 2023. We included studies that focused on BMSM in the Midwestern states; only empirical studies (either quantitative or qualitative or both) were considered. We synthesized the qualitative data and teased out some of the factors inhibiting or facilitating PrEP uptake among BMSM.ResultsWe screened 850 articles, and only 22 (quantitative: 12; qualitative: 8; mixed methods: 2) met our set eligibility criteria. Most of the studies were conducted in Chicago. Most BMSM use oral than injectable PrEP. Uptake of PrEP ranged from 3.0 to 62.8%, and the majority reported a prevalence of less than 15%. The barriers include PrEP awareness, PrEP access, PrEP stigma, side effects, PrEP preference, socioeconomic status, medical insurance and support, partner trust, trust in the health system, and precautions with sexual partners. The identified PrEP facilitators include PrEP use until HIV is eradicated, friend influence, experience with dating men living with HIV, safety, phobia for HIV, disdain for condoms, and power to make decisions.ConclusionOur review summarized patterns of, barriers to, and facilitators of PrEP uptake among BMSM in the Midwest, United States. The low PrEP uptake of BMSM was primarily attributed to mistrust in the health system and low socioeconomic status. Multimodal and multilevel strategies are needed to improve PrEP uptake among BMSM, including improving the marketing of PrEP to BMSM and removing financial barriers to accessing PrEP service.